## RS Aggarwal Class 8 Solutions Chapter 7 Factorisation Ex 7A

These Solutions are part of RS Aggarwal Solutions Class 8. Here we have given RS Aggarwal Solutions Class 8 Chapter 7 Factorisation Ex 7A.

**Other Exercises**

- RS Aggarwal Solutions Class 8 Chapter 7 Factorisation Ex 7A
- RS Aggarwal Solutions Class 8 Chapter 7 Factorisation Ex 7B
- RS Aggarwal Solutions Class 8 Chapter 7 Factorisation Ex 7C
- RS Aggarwal Solutions Class 8 Chapter 7 Factorisation Ex 7D
- RS Aggarwal Solutions Class 8 Chapter 7 Factorisation Ex 7E

**Factorize :**

**Question 1.**

**Solution:**

(i) 12x + 15 = 3(4x + 5) {HCF of 12 and 15 = 3)

(ii) 14m – 21 = 7(2m – 3) {HCF of 14 and 21 = 7)

(iii) 9n – 12n^{2} = 3n(3 – 4n) Ans.{HCF of 9 and 12 = 3}

**Question 2.**

**Solution:**

(i) 16a^{2} – 24ab = 8a(2a – 3b) { HCF of 16 and 24 = 8)

(ii) 15ab^{2} – 20a^{2}b = 5ab(3b – 4a) {HCF of 15 and 20 5}

(iii) 12x^{2}y^{3} – 21x^{3}y^{2}= 3x^{2}y^{2}(4y – 7x) Ans. {HCF of 12 and 21 = 3)

**Question 3.**

**Solution:**

(i) 24x^{3} – 36x^{2}y = 12x^{2}(2x – 3y) {HCF of 24 and 36 = 12}

(ii) 10x^{3} – 15x^{2} = 5x^{2}(2x – 3) {HCF of 10, 15 = 5}

(iii) 36x^{3}y – 60x^{2}y^{3}z = 12x^{2}y (3x – 5y^{2}z) {HCF of 36 and 60 = 12}

**Question 4.**

**Solution:**

(i)9x^{3} – 6x^{2} + 12x

= 3x(3x^{2} – 2x + 4) {HCF of 9, 6, 12 = 3)

(ii)8x^{2} – 72xy + 12x

= 4x(2x – 18y + 3) (HCF of 8, 72, 124)

(iii)18a^{3}b^{3} – 27a^{2}b^{3} + 36a^{3}b^{2}

= 9a^{2}b^{2}(2ab – 3b + 4a) Ans.{HCF of 10, 27, 36 = 9)

**Question 5.**

**Solution:**

(i) 14x^{3} + 21x^{4}y – 28x^{2}y^{2}

= 7x^{2} (2x + 3x^{2}y – 4y^{2}) {HCF of 14, 21 28 = 7)

(ii) – 5 – 10t + 20t^{2}

= – 5(1 + 2t – 4t^{2}) Ans. {HCF of 5, 10, 20=5)

**Question 6.**

**Solution:**

(i) x(x + 3) + 5(x + 3)

=(x + 3)(x + 5)

(ii) 5x(x – 4) – 7(x – 4)

= (x – 4) (5x – 7)

(iii) 2m (1 – n) + 3(1 – n)

= (1 – n) (2m + 3) Ans.

**Question 7.**

**Solution:**

6a(a – 2b) + 5b(a – 2b)

= (a – 2b) (6a + 5b) Ans.

**Question 8.**

**Solution:**

x^{3}(2a – b) + x^{2}(2a – b)

=x^{2}(2a – b)(x + 1)Ans.

**Question 9.**

**Solution:**

9a(3a – 5b) – 12a^{2}(3a – 5b)

= 3a (3a – 5b) (3 – 4a) Ans.

**Question 10.**

**Solution:**

(x + 5)^{2} – 4(x + 5)

= (x + 5)(x + 5 – 4)

=(x + 5)(x + 1)Ans.

**Question 11.**

**Solution:**

3(a – 2b)^{2} – 5 (a – 2b)

= (a – 2b) {3(a – 2b) – 5}

= (a – 2b) (3a – 6b – 5) Ans.

**Question 12.**

**Solution:**

2a + 6b – 3 (a + 3b)^{2}

= 2(a + 3b) – 3(a + 3b)^{2}

= (a + 3b){ 2 – 3 (a + 3b)}

= (a + 3b) (2 – 3a – 9b) Ans.

**Question 13.**

**Solution:**

16(2p – 3q)^{2} – 4 (2p – 3q)

= 4(2p – 3q) {4(2p – 3q) – 1}

= 4(2p – 3q) (8p – 12q – 1) Ans.

**Question 14.**

**Solution:**

x(a – 3) + y (3 – a)

= x(a – 3) – y(a – 3)

= (a – 3) (x – y) Ans.

**Question 15.**

**Solution:**

12(2x – 3y)^{2} – 16(3y – 2x)

= 12(2x – 3y)^{2} + 16(2x – 3y)

= 4(2x – 3y) {3(2x – 3y) + 4}

= 4(2x – 3y) (6x – 9y + 4) Ans.

**Question 16.**

**Solution:**

(x + y)(2x + 5) – (x + y)(x + 3)

= (x + y)(2 + 5 – x – 3)

= (x + y)(x + 2) Ans.

**Question 17.**

**Solution:**

ar + br + at + bt

= r(a + b) + t(a + b)

= (a + b) (r + t) Ans.

**Question 18.**

**Solution:**

x^{2} – ax – bx + ab

= x(x – a) – b(x – a)

= (x – a)(x – b)Ans.

**Question 19.**

**Solution:**

ab^{2} – bc^{2} – ab + c^{2}

= ab^{2} – ab – bc^{2} + c^{2}

= ab(b – 1) – c^{2}(b – 1)

= (b – 1) (ab – c^{2}) Ans.

**Question 20.**

**Solution:**

x^{2} – xz + xy – yz

= x(x – z) + y(x – z)

= (x – z)(x + y)Ans.

**Question 21.**

**Solution:**

6ab – b^{2} + 12ac – 2bc

6ab + 12ac – b^{2} – 2bc

= 6a(b + 2c) – b(b + 2c)

= (b + 2c) (6a – b) Ans.

**Question 22.**

**Solution:**

(x – 2y)^{2} + 4x – 8y

= (x – 2y)^{2} + 4(x – 2y)

= (x – 2y)(x – 2y + 4)Ans.

**Question 23.**

**Solution:**

y^{2} – xy(1 – x) – x^{3}

y^{2} – xy + x^{2}y – x^{2}

= y(y – x) + x^{2} (y – x)

= (y – x)(y + x^{2})Ans.

**Question 24.**

**Solution:**

(ax + by)^{2} + (bx – ay)^{2}

= a^{2}x^{2} + b^{2}y^{2} + 2abxy + b^{2}x^{2} + a^{2}y^{2} – 2abxy

= a^{2}x^{2} + b^{2}y^{2} + b^{2}x^{2} + a^{2}y^{2}

= a^{2}x^{2} + b^{2}x^{2} + a^{2}y^{2} + b^{2}y^{2}

= x^{2}(a^{2} + b^{2}) + y^{2}(a^{2} + b^{2})

= (a^{2} + b^{2}) (x^{2} + y^{2}) Ans.

**Question 25.**

**Solution:**

ab^{2} + (a – 1)b – 1

= ab^{2} + ab – b – 1

= ab(b + 1) – 1(b + 1)

= (b + 1) (ab – 1) Ans.

**Question 26.**

**Solution:**

x^{3} – 3x^{2} + x – 3

= x^{2}(x – 3) + 1(x – 3)

(x – 3)(x^{2} + 1)Ans.

**Question 27.**

**Solution:**

ab (x^{2} + y^{2}) – xy (a^{2} + b^{2})

= abx^{2} + aby^{2} + xya^{2} – xyb^{2}

= abx^{2} – xya^{2} – xyb^{2} + aby2

=ax(bx – ay) – by(bx – ay)

= (bx – ay) (ax – by) Ans.

**Question 28.**

**Solution:**

x^{2} – x (a + 2b) + 2ab

= x^{2} – xa – 2bx + 2ab

= x(x – a) – 2b(x – a)

= (x – a)(x – 2b)

Hope given RS Aggarwal Solutions Class 8 Chapter 7 Factorisation Ex 7A are helpful to complete your math homework.

If you have any doubts, please comment below. Learn Insta try to provide online math tutoring for you.

Prince jha says

Good explanation

Sajid says

Fantastic bava